Dirāsah Tahlīliyah Linushush Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Alrābi’ Al ibtidāī Liwizārah Alsyu`ūwn Aldīniyah Al Indūnīsiyah ām 2020 (Alfashl Alawwal Hatā Alfashl Al tsālits Namūdzajān) - Sabrur Rahma; Mulyadi (Mauriduna: Journal of Islamic Studies, 2022)
This study aimed to know the quality of the texts in the Arabic language book of the Ministry of Religious Affairs for the fourth grade of primary school, from an educational, psychological, and cultural point of view. As well as from the linguistic point of view to know the correctness of the grammar, spelling and syntax in the texts of this book.This study is based on the analytical descriptive approach. This study begins with the process of reading, analyzing, then criticizing, and drawing conclusions. This research is a qualitative library research.The study proved that the texts of the Arabic language book for the fourth grade of the Ministry of Religious Affairs in general are of good quality and are valid from an educational, psychological and cultural point of view for Indonesians. This result came after the researcher’s review and analysis of the book Penelitian ini bertujuan untuk mengetahui kualitas teks dalam buku bahasa Arab Kementerian Agama untuk kelas IV sekolah dasar, ditinjau dari segi pendidikan, psikologis, dan budaya. Serta dari sudut pandang linguistik untuk mengetahui kebenaran tata bahasa, ejaan dan sintaksis dalam teks-teks buku ini. Penelitian ini didasarkan pada pendekatan deskriptif analitis.Penelitian ini diawali dengan proses membaca, menganalisis, kemudian mengkritisi, dan menarik kesimpulan. Penelitian ini merupakan penelitian kualitatif kepustakaan.Hasil penelitian membuktikan bahwa teks-teks buku bahasa Arab kelas IV Kementerian Agama secara umum memiliki kualitas yang baik dan valid dari segi pendidikan, psikologis, dan budaya bagi masyarakat Indonesia. Hasil ini muncul setelah peneliti melakukan review dan analisis terhadap buku tersebut